2014
DOI: 10.1007/s00592-014-0661-4
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin status and its relation with depression, cognition and neuropathy in patients with type 2 diabetes mellitus using metformin

Abstract: Cobalamin deficiency was associated with an increased risk of depression and worse cognitive performance, while holoTCII was not. Screening for cobalamin deficiency may be warranted in diabetes patients using metformin. Physicians should consider a cobalamin deficiency in diabetes patients using metformin with a depression or cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
1
26
0
1
Order By: Relevance
“…Other studies have demonstrated a close association between vitamin B 12 deficiency and long term use and high dose metformin therapy [36, 11, 13, 23]. Metformin has been shown to reduce calcium bioavailability which affects ileal vitamin B12 absorption [1, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated a close association between vitamin B 12 deficiency and long term use and high dose metformin therapy [36, 11, 13, 23]. Metformin has been shown to reduce calcium bioavailability which affects ileal vitamin B12 absorption [1, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies reported that the vitamin deficiency among metformin-treated patients was associated with worsened cognitive performance and increased risk of depression (107,110).…”
Section: Neuropsychiatric Manifestationsmentioning
confidence: 99%
“…Biemans et al (107) Four primary care centers, the Netherlands Cross-sectional study. Metformintreated T2DM patients were divided into vitamin B12-deficient and normal groups.…”
Section: Dementioning
confidence: 99%
“…Separately, metformin, which is commonly used to decrease insulin resistance in T2D, has been suggested to have a side effect that results in the inhibition of vitamin‐B 12 absorption in the digestive tract through a mechanism completely different from that suggested for H pylori . Thus, in the guidelines for the treatment of diabetes, T2D patients using metformin have been recommended to check their serum vitamin‐B 12 levels regularly and use vitamin‐B 12 supplements when necessary 8,25 . This study examined the H pylori infection status and vitamin‐B 12 levels in T2D patients receiving metformin treatment and found that the mean serum vitamin‐B 12 level was significantly lower and the rate of vitamin‐B 12 deficiency was significantly higher in diabetic patients with H pylori infection compared to those without H pylori infection.…”
Section: Discussionmentioning
confidence: 99%